Microstructural Analysis And Mechanical Properties Of LM6 Alloy Processed By Cooling Slope Casting - Salleh, Mohd Shukor; Mohamad Ishak, Nurul Naili; Safian, Mohd Azizul Hikmi; Yahaya, Saifudin Hafiz (Penerbit UTeM, 2016)
-